Density distributions and form factors of the exotic 8B nucleus - Majeed, W. Z. (Iraqi Journal of Physics, 2019)
Results of charge, neutron and matter densities and related form factors for one- proton halo nucleus 8B are presented using a two- frequency shell model approach. We choose a model space for the core of 7Be different from that of the extra one valence proton. One configuration is assumed for the outer proton to be in 1p1/2 - shell. The results of the matter density distributions are compared with those fitted to the experimental data. The calculated proton and matter density distributions of this exotic nucleus exhibit a long tail behavior, which is considered as a distinctive feature of halo nuclei. Elastic electron scattering form factors of this exotic nucleus are also studied. The effects of the proton halo on the electron scattering form factors are analyzed. The form factors of the exotic unstable 8B nucleus are compared with those of the stable 10B nucleus. The differences between the results of unstable 8B and stable 10B nuclei come from the long tail in the density distribution of the last proton.